Methodological intervention with soccer coaches to improve athlete-perceived coaching competency, satisfaction with the coach, enjoyment and intention to persist - Pulido, J. J.; Leo, F. M.; González-Ponce, I.; López-Gajardo, M. A.; Sánchez-Oliva, D. (International Journal of Sports Science & Coaching, 2021)
Objectives: The purpose of the study was to assess the effect of a coaching intervention on soccer athletes` perceptions of the coaches` competencies, enjoyment, satisfaction, and intention to persist in the sport.